On generalization of ⊕-cofinitely supplemented modules - Nisanci, B.; Pancar, A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We study the properties of ⊕-cofinitely radical supplemented modules, or, briefly, cgs^⊕-modules. It is shown that a module with summand sum property (SSP) is cgs^⊕ if and only if M/w Loc^⊕ M (w Loc^⊕ M is the sum of all w-local direct summands of a module M) does not contain any maximal submodule, that every cofinite direct summand of a UC-extending cgs^⊕-module is cgs^⊕, and that, for any ring R, every free R-module is cgs^⊕ if and only if R is semiperfect.